9 Demonstrating the impact of palliative care: a secondary analysis of routinely-collected person-centred outcomes data among patients receiving community palliative care. Issue Volume 11: Issue (2021)Supplement 1 (16th March 2021) - Khamis, Assem; Bradshaw, Andy; Davies, Joanna; Landon, Alison; Dodds, Nigel; Proffit, Amy; George, Rob; Boland, Jason; Santarelli, Martina; Sartain, Kath; Ross, Joy; Richardson, Heather; et al.
Abstract : Background: The aim of this study is to describe the characteristics of patients receiving community palliative care and the impact of community palliative care on their symptoms and concerns using routinely-collected patient-level outcomes data. Methods: Secondary analysis of routinely-collected clinical and outcomes data (patients' demographics, episodes of care, palliative Phase of Illness, and symptoms/concerns using the Integrated Palliative care Outcome Scale; IPOS) from all patients cared for in the community by one hospice, between June - November 2019. We described the characteristic of patients, their episode of care, and their Phase of Illness at first contact with the community service. We compared community patients based on their episode outcome (alive versus died, at end of episode) and the impact of community palliative care over the first Phase of Illness. Caldicott Guardian approval was received for analysis of this anonymized data. Results: 881 patients received 916 complete episodes of community-based palliative care between June-November 2019. For 916 episodes of care, the median age of community patients was 79 years with IQR (69 '' 87); 66% had cancer. Palliative Phase of Illness was stable (17%), unstable (28%), deteriorating (41%) and dying (14%) at the start of episode of care. By the first Phase change; mean 'pain' score reduced from 1.3 to 1.2 (30% of 158 patients with moderate/severe/overwhelming pain improved); mean 'breathlessness' score reduced from 0.8 to 0.7, (with 39% of 87 patients with moderate/severe/overwhelming breathlessness improved); mean 'anxiety' score reduced from 1.2 to 1.0 (with 31% of 84 patients with moderate/severe/overwhelming anxiety improved); and mean 'feeling depressed' score reduced from 0.7 to 0.6 (with 42% of 45 patients with moderate/severe/overwhelming depressed mood improved). Conclusions: This analysis demonstrates, for the first time in the UK, how community palliative care teams can systematically use routinely-collected outcomes data to demonstrate the positive impact of the care they provide. Funding: Supported by Yorkshire Cancer Research (L412)